Broadband Spintronic Terahertz Emitter with Magnetic‐Field Manipulated Polarizations. Issue 20 (26th July 2019) - Kong, Deyin; Wu, Xiaojun; Wang, Bo; Nie, Tianxiao; Xiao, Meng; Pandey, Chandan; Gao, Yang; Wen, Lianggong; Zhao, Weisheng; Ruan, Cunjun; Miao, Jungang; Li, Yutong; et al.
Abstract: Flexible manipulation of terahertz wave polarizations during the generation process is very important for terahertz applications, especially for the next‐generation on‐chip functional terahertz sources. However, current terahertz emitters cannot satisfy such demand, hence calling for new mechanisms and conceptually new terahertz sources. Here an efficient and broadband terahertz source with magnetic‐field‐controlled flexible switching for the polarizations between linear and elliptical states in ferromagnetic heterostructures driven by femtosecond laser pulses is demonstrated. More importantly, the chirality, azimuthal angle, and ellipticity of the generated elliptical terahertz wave can be precisely manipulated by harnessing external magnetic fields via effectively tailoring the photoinduced spin currents. Such an ultrafast photomagnetic interaction‐based, magnetic‐field‐controlled, and broadband tunable solid‐state terahertz source integrated with polarization tunability functions not only provides the capability to reveal physical mechanisms of femtosecond spin dynamics, but also demonstrates the feasibility to realize novel on‐chip terahertz functional devices, boosting the potential applications for controlling elementary molecular rotations, phonon vibrations, spin precessions, high‐speed communications, and accelerating the development of ultrafast terahertz optospintronics. Abstract : Flexible manipulation of terahertz wave polarizations during the generation process is very important. Here a terahertz source with magnetic‐field‐controlled polarizations in ferromagnetic heterostructures driven by femtosecond laser pulses is demonstrated. Such source not only provides the capability to reveal physical mechanisms of femtosecond spin dynamics, but also demonstrates the feasibility to realize novel on‐chip terahertz functional devices.